Design of the “Hello Maggot” Program E-book For Pesan Trend Educational Area Visitor Age 18-24 Years - Karlina, Nichi Hana; Widiansyah, Aldika; Rizkiani, Meti Agni (Research Collaboration Community (Rescollacom), 2024)
Pesan Trend is a non-formal education area for young people, Pesan Trend has a goal to convey good messages to become a trend in the midst of society. One of the focuses movement of Pesan Trend is on environmental issues, with the amount of waste currently available, making Pesan Trend moved to breed BSF (Black Soldier Fly) fly larvae to be able to decompose organic waste. The use of media in the form of E-books is considered to be able to help the teaching and learning activities at Pesan Trend which use the concept of tours and simulations in their teaching and learning activities. So it requires flexibility in the learning process and requires media that is easy to use and not easily damaged. The method used in this design is a qualitative method. Data collection techniques in this design use interview techniques and direct observation to the Pesan Trend education area. The design of this E-book educational media is based on theories related to editorial, visual communication design science, AISAS, icons, photography, and other theories related to design. The design of the E-book with the title